Pengaruh Model Pembelajaran Core Mathematic Terhadap Hasil Belajar Matematika Siswa Kelas III di SDIT Fathona Palembang - Ghoibah, Siti Nur; Nurlaeli; Husni, Miftahul; Elhefni; Aquami (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research focuses on the application of the core mathematic learning model in class III, with the aim of knowing its effect on students' mathematics learning outcomes. Inappropriate teaching methods can make it difficult for students to achieve good learning outcomes, so it is necessary to understand and apply more varied learning models. This study used an experimental design with a pretest and posttest approach in one group, involving all third grade students of SDIT Fathona Palembang, totalling 23 students as samples. Data were obtained through learning outcome tests conducted before and after the application of the core mathematic learning model. Data analysis was conducted using paired sample t-test with 95% significance level. The results of the analysis showed a sig. (2-tailed) value of 0.000 <0.05, which means H0 is rejected and H1 is accepted, indicating a positive effect of the application of the learning model on students' mathematics learning outcomes. This finding confirms that the application of the core mathematic learning model can improve students' understanding and academic achievement. As a follow-up, it is recommended that teachers at SDIT Fathona Palembang receive training to implement this method more effectively. Further research is also suggested to involve other classes and different learning approaches, in the hope of creating an interactive and enjoyable educational environment, as well as improving overall student achievement.